2006
DOI: 10.1080/00498250600861751
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of 50 xenobiotic transporter genes in humans and pre-clinical species: A resource for investigations into drug disposition

Abstract: Carrier-mediated transporters play a critical role in xenobiotic disposition and transporter research is complicated by species differences and their selective tissue expression. The purpose of this study was to generate a comprehensive data set of xenobiotic transporter gene expression profiles in humans and the pre-clinical species mouse, rat, beagle dog and cynomolgus monkey. mRNA expression profiles of 50 genes from the ABC, SLC and SLCO transporter superfamilies were examined in 40 human tissues by microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
231
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(245 citation statements)
references
References 80 publications
12
231
0
2
Order By: Relevance
“…OCT physiology in tissues such as the liver, gut and kidneys has by and large been well characterised (Nies et al, 2011), nonetheless, the lungs remain somewhat understudied in this regard. Moreover, OCT expression data concerning the respiratory epithelium is often limited to gene or PCR-based in vitro studies (Bleasby et al, 2006;Courcot et al, 2012;Endter et al, 2009;Mukherjee et al, 2012) and only a small number of reports show OCT immunocytochemistry or indeed transporter function (Lips et al 2005;Macdonald et al, 2013;Nakanishi et al, 2013). Very recently, it has been shown by our group that β 2 agonists interact with OCT at the lung epithelium (Salomon et al, 2015), however, the clinical relevance of these findings are not fully understood to date.…”
Section: Introductionmentioning
confidence: 91%
“…OCT physiology in tissues such as the liver, gut and kidneys has by and large been well characterised (Nies et al, 2011), nonetheless, the lungs remain somewhat understudied in this regard. Moreover, OCT expression data concerning the respiratory epithelium is often limited to gene or PCR-based in vitro studies (Bleasby et al, 2006;Courcot et al, 2012;Endter et al, 2009;Mukherjee et al, 2012) and only a small number of reports show OCT immunocytochemistry or indeed transporter function (Lips et al 2005;Macdonald et al, 2013;Nakanishi et al, 2013). Very recently, it has been shown by our group that β 2 agonists interact with OCT at the lung epithelium (Salomon et al, 2015), however, the clinical relevance of these findings are not fully understood to date.…”
Section: Introductionmentioning
confidence: 91%
“…[62] Other transporters have been less extensively studies but they are expressed at the brain barriers and, for instance, protease inhibitors have been shown to be substrate of OAT1A2. [63,64] The importance of understanding drug passage across BBB and BCB lies in the modulatory effects on transporters and on the possible influence of genetic polymorphisms affecting enzyme activity or expression. In human primates (using nelfinavir and zosiquidar, a P-gp inhibitor) P-gp blocking was associated with modest increases in CSF concentrations but extensive increments in brain concentrations.…”
Section: Transporters and Pharmacogeneticsmentioning
confidence: 99%
“…The transporter is detected in almost all tissues and is expressed at high levels in adipose tissue, lung, prostate, and skeletal muscle in humans and rodents 42,43 . Further, OCT3 is expressed in the blood brain barrier, placenta, and salivary glands [42][43][44] .…”
mentioning
confidence: 99%
“…The transporter is detected in almost all tissues and is expressed at high levels in adipose tissue, lung, prostate, and skeletal muscle in humans and rodents 42,43 . Further, OCT3 is expressed in the blood brain barrier, placenta, and salivary glands [42][43][44] . Using the Oct3 knockout mouse model, Chen et al showed a 2-fold decrease in the apparent volume of distribution of metformin in knockout compared with wildtype mice after intravenous doses of metformin 15 .…”
mentioning
confidence: 99%